Conviction of the Innocent : Lessons from Psychological Research - Cutler, Brian L. (American Psychological Association, 2012)
"Over the last several decades over 250 citizens convicted of major felonies were found innocent and were exonerated. Today, thanks to the work of psychologists and other criminal justice researchers, the psychological foundations that underlie conviction of the innocent are becoming clear. There is real hope that these findings can lead to positive reforms, reduce the risk of miscarriages of justice, and avoid the consequences of wrongful convictions to victims and society. In this book, editor Brian Cutler presents a state-of-the-field review of current psychological research on conviction of the innocent. Chapter authors investigate how the roles played by suspects, investigators, eyewitnesses, and trial witnesses and how pervasive systemic issues contribute to conspire to increase the risk of conviction of the innocent. The chapters skillfully examine psychological perspectives on such topics as police interrogations, confessions, eyewitness identification, trial procedures, juries, and forensic science, as well as broader issues such as racism and tunnel vision within the justice system. This comprehensive volume represents an important milestone for research on miscarriages of justice. By bringing psychological theories and research to bear on this social problem, the authors derive compelling recommendations for future research and practical reform in police and legal procedures"--Publicity materials. (PsycINFO Database Record (c) 2011 APA, all rights reserved).